Legal foundations for regulating the financial services market in the European Union: conceptual approaches, regulatory mechanisms, and institutional framework - Shevchuk , Oksana; Bereza, Roman (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
The article examines the legal foundations for regulating the financial services market in the European Union, including conceptual approaches, regulatory mechanisms, and institutional frameworks. It has been established that the regulation of the financial services market in the EU is based on principles of transparency, stability, consumer protection, risk prevention, and the avoidance of abuses, aimed at ensuring the effective functioning of financial markets. The role of legal harmonization within the EU internal market is highlighted, as it eliminates barriers between national legal systems and establishes uniform rules for financial intermediaries.The key EU regulatory acts governing the financial market are analyzed, including the MiFID II Directive, MiFIR Regulation, PSD2 Directive, and CRD IV Regulation. Special attention is given to their impact on the banking sector, capital markets, payment systems, and investment companies. The study explores regulatory requirements for licensing, risk management, anti-money laundering, corporate governance, and ensuring the accountability of financial institutions.The institutional structure of financial market regulation is outlined, with a focus on the roles and powers of the European Banking Authority (EBA), the European Securities and Markets Authority (ESMA), and the European Insurance and Occupational Pensions Authority (EIOPA). These bodies are shown to play a key role in supervision, standard harmonization, and coordination among national regulators.The article also addresses the prospects for implementing European regulatory practices in Ukraine's financial services market. The author concludes that adapting Ukrainian legislation to EU norms will enhance market transparency, protect investors' rights, and strengthen the stability of the financial system.